Forced relocation from informal settlements to the periphery and effects on livelihoods: a case of Diepsloot, Johannesburg - Ngcobo, Sibonelo Phiwokwakhe (My University, 2015)
In post-apartheid South Africa, the delivery of low-income housing has been occurring at unprecedented rates since 1994. This means that more and more poor households are gaining access to secure tenure on progressive basis. Unfortunately the new low-income housing townships are often established on cheap peripheral land, adjacent or far beyond the existing apartheid townships. The widespread growth of informal settlements in urban areas has also been occurring at higher rates following the repeal of apartheid laws which restricted rural-urban migration. The growth of informal settlements is nothing but a precise indication of poverty and the desire of the poor to gain access to employment opportunities. However, the link between employment opportunities and home is often provided by transport. Travelling demands money which most of the urban poor rarely have. For the poor, proximity to areas of employment opportunities is key to surviving in urban areas. The consequence of this arrangement is the establishment of informal settlements near places of employment as a way of escaping the cost of transport. Yet the upgrading of well-located informal settlements has not been a preferred and popular strategy for the post-apartheid government as a mechanism for promoting access to opportunities. Instead the focus has largely been on providing access to individual tenure through the delivery of the free-standing housing units on the periphery where land is relatively cheap to accommodate large scale housing delivery. Is this the only factor which had motivated the rural poor to migrate to urban areas in the first place? Which matters most for the urban poor? Is it access to subsidised housing in the urban area only or is the latter. Perhaps it is a combination of both factors. To provide answers to the foregoing questions, the researcher resolved to pose two guiding questions to focus the investigation: What are the effects of relocation to the periphery on household livelihoods and how do relocated households make a living on the periphery....what sort of coping mechanisms are adopted to survive in remote, isolated, low density and sprawling low-income Reconstruction and Development Programme (RDP) townships of the post-apartheid South Africa? The research uses Diepsloot as a case study area because it presents all the necessary traits of a typical post-apartheid South African low-income township which had been used as a northern Johannesburg relocation site. The findings of the research suggest that the only major positive impact which result from relocation, is access to secure tenure while the major negative impact, is the poor location of Diepsloot in relation to major employment opportunities. This finding correlates with the existing literature and the hypothesis of the study.
A research report approved by the Faculty of Engineering and the Built Environment of the University of Witwatersrand for the degree of Master of the Built Environment in housing
Keywords: City planning--South Africa; Squatter settlements--South Africa--Johannesburg--Diepsloot